UPAYA MENINGKATKAN AKTIVITAS BELAJAR DAN KETERAMPILAN MEMBACA GAMBAR TEKNIK MENGGUNAKAN METODE DISKUSI, DENGAN GAMBAR BERSERI PADA SISWA KELAS XI M SMK GANESHA METRO - Bambang Sigit Driyo Handono (Universitas Muhammadiyah Metro, 2015)
In keeping up with the development of information technology, Engineering Drawing still requires the solid base of drawing which needs to be mastered for all machinery users. Mastering Engineering drawing covers supporting knowledge to draw manually or computer assisted. Reality found, the skill of reading engineering drawing students of Vocational High School (known as SMK) Ganesha Metro was still low. It was low because their learning activity was also low. An instruction using discussion method and engineering serial pictures is a method strongly suspected able to provide more chances in developing students active role to get involved both physically and emotionally during the instructional process. It appeared that the method combined by the media was not maximized to empower students potency. The method of the research was Classroom Action Research (CAR). CAR is a research the improve teaching practice and learning achievement. It required 2 two cycles with a precycle treatment and test. The research was carried out at SMK Ganesha Metro. It involved students class XI M as many as 33. It was odd semester of Academic Year 2011/2012. The research took place for three months, from September to November 2011. It was done in accordance with time table scheduled by the school. Conclusion made by the researcher after deep analysis to data and findings. The improvement of learning activity and the skill of reading engineering drawing could be achieved through the implementation of discussion method and engineering pictures series. Series pictures were used at cycle II to facilitate students understanding toward the reading of engineering drawing, both reading and the skill of drawing. The implementation of discussion method was arranged in a sequence of starting from classroom discussion, small group discussion, and panel discussion. Some drawing assignments were given earlier to abridge the skill development and learning material mastery through self exercise. The implementation of discussion method with the sequence meant to provide wider chance for the students to understand the learning materials substance.